The Role of Islamic Financial Literacy in Shaping Economic Behavior: Evidence from Generation Z - Putri Muninggar; Moh Shadam Taqiyyuddin Azka; Furqonul Haq; Ahmad Febriyanto (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
This study aims to examine the influence of Islamic financial literacy on the financial management behavior of Generation Z in Indonesia by extending the Theory of Planned Behavior (TPB). It explores how Islamic financial literacy shapes individuals’ attitudes, subjective norms, and perceived behavioral control, which subsequently influence their Sharia-compliant financial decisions. This research employs a quantitative approach, specifically using Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. The findings reveal that Islamic financial literacy significantly enhances attitudes, subjective norms, and perceived behavioral control, all of which positively influence Islamic financial management behavior. This behavior is closely linked to improved financial decision-making, including saving habits, ethical investment choices, and long-term financial stability. By promoting Islamic financial literacy, this research highlights potential policy interventions to enhance financial inclusion and encourage participation in the Sharia-compliant financial sector. Strengthening financial capabilities among Generation Z can contribute to broader macroeconomic goals, such as reducing vulnerability to financial shocks and fostering equitable economic growth. This study contributes to the literature by extending the Theory of Planned Behavior to the Islamic financial context, specifically focusing on a generational cohort that will play a critical role in the future of Indonesia's Islamic economy.